Correlation between Modified Tal Score and Oxygen Saturation Values Detected by Pulse Oximeter in Children with Bronchiolitis (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: A number of clinical scoring systems have been used for risk stratification of children with bronchiolitis, most of them have not validate in our setting. Modified Tal’s Score (MTS) is one of such clinical score. This study aimed to determine the relation between MTS and oxygen saturation (SpO2) measured by pulse Oximeterin children with acute bronchiolitis patients admitted to a tertiary-level hospital in Bangladesh. . Materials and methods: This cross-sectional study included 251 children aged